KNOWLEDGE, PERCEPTION, PRACTICE OF PERSONAL HYGIENE AMONG SECONDARY SCHOOL STUDENTS IN IBADAN NORTH WEST LOCAL GOVERNMENT AREA, IBADAN, OYO STATE, NIGERIA (2015)
Personal Hygiene (PH) is fundamental to the prevention and control of communicable diseases and maintaining good health. Many communicable diseases of public health importance, which affect Secondary School Students (SSS), are caused by poor PH. Despite awareness of personal hygiene in Nigeria, there is the need to identify the level of practice by SSS. This study was therefore designed to determine the knowledge, perception and practices of PH among SSS in Ibadan North West Local Government Area (LGA). A cross-sectional study design was used. Public Junior Secondary School (PJSS) and Senior Secondary School (PSSS) in the LGA were stratified and three of 17 PJSS and two of 9 PSSS selected through simple random sampling. Systematic random sampling was used in selecting 476 respondents out of 724 students. An interviewer-administered semi-structured questionnaire, which included a 28 knowledge, 9 perception, and 31 practice scales, was used for data collection. Knowledge scores of ≤ 10, > 10 to < 20 and ≥ 20 were rated as poor, fair and good respectively. Perception scores of > 4 were classified as positive while practice scores of > 15 were rated as good. Two different sets of observational checklists were used to assess respondents’ physical appearance, classrooms and the schools’ environment. Data were analysed using descriptive statistics and Chi-square test at 5% level of significance. Respondent’s mean age was 13.9±2.0, 55.7% were females and 60.3% were in PJSS. Mean knowledge, perception and practice scores were 17.8±3.9, 5.8±2.1 and 15.4±4.7 respectively. Respondents with poor, fair and good knowledge in PJSS were 4.9%, 80.1% and 15.0%, while those in the PSSS were 0.5%, 56.1% and 43.4% respectively. Majority (72.9%) had positive perception of PH, 48.8% of the respondents in PJSS and 54.0% in PSSS engaged in good practices. The opinion of 45.6% was that hand washing with clean water alone was enough to make hands free of germs. Bad PH practices among respondents included sharing of bathing sponge with others (73.8%), cutting of fingernails with teeth (40.3%) and cleaning of nostrils with fingers (31.5%). Significantly more respondents (66.4%) with good knowledge of PH engaged in good PH practices compared to those with poor knowledge that engaged in good PH practices (46.7%) with P-value of 0.01. Also more respondents (58.0%) with positive perception engaged in good practices, than 33.3% with negative perception who engaged in good PH practices. Majority (62.0%) of the observed respondents had neatly combed hair, 87.1% had clean teeth, 98.0% had foot wear on and 72.3% wore stockings. Only 2.9% of the classes observed had bowls for water, none had either soap or towel and only 17.6% of the classes had dustbins. The median number of toilets in the schools was 3.0 (range 0-6) and 80.0% of the schools had dug wells. Majority of the respondents had positive perception of personal hygiene and their knowledge was fair. Furthermore, some of their practices have potential for putting them at risk of infection. Training and the provision of adequate sanitary facilities are needed to address the challenges.